Lords of the land indigenous property rights and the jurisprudence of empire - Hickford, Mark. (Oxford : Oxford University Press, 2011)
Through focusing on the political history of New Zealand during its imperial settlement, this book offers a fresh assessment of the history of indigenous property rights. It shows how native title became a constitutional frame within which political authority was formed and contested at the heart of empire and the colonial peripheries.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Maori (New Zealand people) -- Land tenure; Maori (New Zealand people) -- Legal status, laws, etc; Land settlement -- Law and legislation -- New Zealand; Land settlement -- New Zealand -- History -- 19th century